SMART AGRO MOBILE: DEVELOPMENT OF AN INTELLIGENT MOBILE SYSTEM FOR MANAGING AGRICULTURAL PROCESSES BASED ON ARTIFICIAL INTELLIGENCE - G‘iyosiddinov Tohirjon Egamberdi o‘g‘li (International Journal of Literature and Language Studies, 2026)
This paper presents the conceptual design of Smart Agro Mobile, an intelligent mobile platform based on Artificial Intelligence (AI), Internet of Things (IoT), cloud computing, and mobile technologies for smart agricultural management. The proposed system enables real-time monitoring, analysis, prediction, and automatic control of greenhouse and open-field agricultural environments. The architecture integrates ESP32 microcontrollers, wireless sensor networks, MQTT communication protocol, Firebase cloud database, machine learning algorithms, convolutional neural networks (CNN), Long Short-Term Memory (LSTM), and Android mobile applications. Experimental evaluations indicate that the system can reduce water consumption by 35–50%, electricity usage by 20–30%, labor costs by nearly 40%, while increasing crop productivity by approximately 20–30%. The proposed Smart Agro Mobile platform represents a promising solution for the digital transformation of agriculture in Uzbekistan.